2010
DOI: 10.1016/j.freeradbiomed.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 and MitoTEMPO partially prevent mitochondrial permeability transition pore opening, necrosis, and mitochondrial apoptosis after ATP depletion recovery

Abstract: Generation of excessive reactive oxygen species (ROS) leads to mitochondrial dysfunction, apoptosis and necrosis in renal ischemia-reperfusion (IR) injury. Previously we showed that lentiviral vector mediated over-expression of superoxide dismutase-1 (SOD1) in proximal tubular epithelial cells (LLC-PK 1 ) reduced cytotoxicity in an in vitro model of IR injury. Here, we examined the effects of SOD1 over-expression on mitochondrial signaling following ATP depletion-recovery (ATP-DR). To examine the role of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 51 publications
6
80
0
Order By: Relevance
“…Modulation of mitochondrial Ca 2+ uptake or release alters oxidation within hair cells exposed to aminoglycosides in a manner consistent with their central involvement in the process. Furthermore, aminoglycoside protection afforded by mitoTEMPO lies in stark contrast to that of TEMPOL despite the ability of both compounds to act as electron sinks (65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of mitochondrial Ca 2+ uptake or release alters oxidation within hair cells exposed to aminoglycosides in a manner consistent with their central involvement in the process. Furthermore, aminoglycoside protection afforded by mitoTEMPO lies in stark contrast to that of TEMPOL despite the ability of both compounds to act as electron sinks (65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot and immunofluorescence assays demonstrated that SSBP1 deficiency resulted in lower E-cadherin expression and higher N-cadherin and fibronectin expression. Of note, treatment with GW788388 and MitoTEMPO, an inhibitor of TGFb/SMAD3 signaling and mitochondrial ROS, respectively (26)(27)(28), mitigated the effects of SSBP1 deficiency on the cell invasive ability and EMT (Fig. 5D-G).…”
Section: Ssbp1 Regulates Tgfb Signaling and Tgfb-induced Epithelialtomentioning
confidence: 95%
“…Antioxidants such as NAC, Mito-TEMPO, and SOD have also been observed to alleviate mitochondrial fragmentation and apoptosis, as well as reduce cellular senescence and the opening of mitochondrial permeability transition pores (45,73). Although the use of antioxidants in the treatment of COPD is limited, investigations underlying the therapeutic index of radical-scavenging pharmaceuticals are currently underway.…”
Section: Antioxidant Therapeutic Strategies In Copd-targeting Oxidatimentioning
confidence: 99%